State and enterprise information security management: legal and organizational aspects - Panchenko, Volodymyr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The components of the state information policy on information security and the basic activities of public authorities in this field are reviewed in the article. The internal and external information challenges facing Ukraine and ways of ensuring information security are analyzed. Information security is seen as a component of national security, as well as a global problem of information security, information space, information sovereignty and information support decision-making.The article is devoted to the review of approaches to the essence of threats to information security and politico-juridical analysis of threats to information security of Ukraine at the present stage. The threats of information security are analysed in the context of the system of threats of national security.On base of the analysis of the condition normative-legal regulation to information safety of the Ukraine are determined main value and defect in normative field state on provision of information security.The definition of information security of the enterprise is given. The basic goals, objectives, principles and types of threats. At their core formed methodical approach to developing the information security systems of industrial enterprises.The proposed enterprise information security system is regarded as a model of information warfare with the factors of internal and external environment, based on the analysis of modern approaches to the definition of information security, and on a synthesis of theoretical positions and experience of functioning of the organizations.The use of the developed approach the Holy Practice of management of industrial enterprises will help to increase the efficiency of development, implementation and use of information security and prevent system or methodological errors at each stage.